“Pregnancy Is Not a Disease”: Conscientious Refusal and the Argument from Concepts - Brudney, Daniel (The Hastings Center report, 2014)
In many American states, a health care worker has a legal right to immunity from employer sanction if she refuses to perform actions at odds with her conscience: she has a legal right to accommodation of her conscientious beliefs. A number of arguments have been advanced to defend or reject this right. These have tended to focus on the possibly conflicting interests of the health care worker and the patient. Recently, however, a new argument has been proposed to justify immunity from employer sanction. This argument rests on the premise that the scope of the very concepts of medicine and disease circumscribes the scope of proper medical practice. Procedures and activities that fall outside the scope of medicine and disease are not properly within the brief of health care personnel. This argument is important because, in principle, it stands outside the balancing of interests. Its central claim is nonsectarian—namely, that a person ought to do her job but need not do what is not her job. This claim avoids taking any stand in the culture wars. It is merely a claim about the logic of the concept “professional.” The medical professional who refuses to perform a procedure is not asking for special treatment. On the contrary, she is asking to be treated normally—in accordance with the normal contours of her job. Of course, other arguments also seek to justify health care providers’ immunity from employer sanction. Ultimately, these different arguments need to be prized apart and scrutinized one by one. This essay focuses on the argument from the concepts of medicine and disease, as a down payment on that larger project.